Exosomal communication by metastatic osteosarcoma cells modulates alveolar macrophages to an M2 tumor-promoting phenotype and inhibits tumoricidal functions. (1st January 2020) - Wolf-Dennen, Kerri; Gordon, Nancy; Kleinerman, Eugenie S.
ABSTRACT: Osteosarcoma metastasizes to the lung, and there is a link between the predominance of tumor-promoting immunosuppressive M2 macrophages in the metastases and poor patient survival. By contrast, M1 macrophage predominance correlates with longer survival. M2 macrophages can be induced by various stimuli in the tumor microenvironment, including exosomes, which are 40- to 150-nm vesicles that are involved in intercellular communication and contribute to tumor progression and immune evasion. Recognizing that tumor cells can influence the tumor microenvironment to make it more permissive and because of the link between M2 dominance and curtailed patient survival, we evaluated the effect of exosomes from non-metastatic K7 and Dunn osteosarcoma cells and the metastatic sublines K7M3 and DLM8 on macrophage phenotype and function. Incubating MHS mouse alveolar macrophages with K7M3 and DLM8 exosomes induced expression of IL10, TGFB2, and CCL22 mRNA (markers of M2 macrophages) and decreased phagocytosis, efferocytosis, and macrophage-mediated tumor cell killing. In contrast, exosomes from non-metastatic K7 or Dunn cells did not inhibit phagocytosis, efferocytosis, and macrophage-mediated cytotoxicity or induce increased expression of IL10, TGFB2 or CCL22 mRNA. In addition, metastatic osteosarcoma cell exosomes significantly increased the secretion of TGFB2, a key signaling pathway associated with tumor- mediated immune suppression. Finally, the inhibition of TGFB2 reversed the suppressive activity of alveolar macrophages exposed to metastatic osteosarcoma cell exosomes. Our data suggest that the exosomes from metastatic osteosarcoma cells can modulate cellular signaling of tumor-associated macrophages, thereby promoting the M2 phenotype and creating an immunosuppressive, tumor-promoting microenvironment through the production of TGFB2.